Postoperative outcomes after splenectomy: a 20-year single-center experience in Colombia - Carlos Eduardo Rey Chaves; Sebastián Díaz; David Gómez Garnica; Oscar Cardenas; Paula Noguera; Manuela Ortíz Marín; Vanessa Velandia; Danny Conde; María Camila Rojas Gómez; María Gómez Zuleta (BMC Surgery)
Abstract Background Splenectomy indications are well documented; however, several infectious complications and potentially life-threatening conditions could arise after splenectomy. We aim to describe a 20-year single-center experience of postoperative outcomes after splenectomy and perform a subgroup analysis according to approach and surgical setting with a 30-day, 90-day, and 1-year follow-up. Study design A retrospective cohort study was conducted between 2003 and 2023. We included all patients aged 18 years and older who underwent splenectomy. A description of clinical and operative variables with infectious outcomes was performed. Subgroup analyses were performed between open or laparoscopic approach and surgical setting. Results A total of 134 patients were included. Female patients constituted 52.99% (n = 71) of cases, with a mean age of 51.01 ± 20.79 years. The most frequent surgical indication for splenectomy was trauma in 31.34% (n = 42), and a laparoscopic approach was indicated in 41.79% (n = 56). Overwhelming post-splenectomy syndrome (OPSI) was evidenced in 2.24% (n = 3) of the population. Surgical characteristics such as operative time, intraoperative blood loss, and intensive care requirement and unit length of stay were higher in open and trauma patients. Conclusion Our data describe the demographic, clinical and operative characteristics of patients undergoing splenectomy in Colombia, providing a solid basis for future research. The results obtained on overwhelming postsplenectomy syndrome (OPSI) and postoperative complications are comparable with those reported in the international literature, reinforcing the validity of our findings. Further prospective studies in this population are needed to optimize management strategies and improve clinical outcomes, particularly in higher risk subgroups.